ESTIMASI CADANGAN KARBON MENGGUNAKAN CITRA SATELITE SENTINEL – 2 MSI - Ratih Nur Islamiah; Ahmad Jauhari; Abdi Fithria (Jurnal Sylva Scienteae, 2023)
Estimating carbon stock in tropical rainforests is an important indicator of environmental health, and increasingly important in the era of climate change mitigation. In this study, we used Normalized Difference Vegetation Index (NDVI) classification on Sentinel-2 MSI imagery to estimate carbon reserves in the tropical rainforest of the Special Purpose Forest Area (KHDTK) of Lambung Mangkurat University. Sentinel 2 MSI satellite imagery was used to obtain information on NDVI values and land cover, while NDVI classification was used to connect this information with field data on carbon reserve calculations. The results of the study based on NDVI classification values in KHDTK varied between 0.0716 and 0.83424, consisting of five land cover classes: open land, shrubs, plantations or young secondary forests, intermediate secondary forests, and mature secondary forests. The carbon stock was obtained from 47% of the biomass calculated using existing allometric equations, with biomass measurements taken on trees with a diameter of 10 centimeters or more. The five land cover classes classified yielded a carbon stock of 6.05 tons/ha for open land, 13.40 tons/ha for shrubs, 21.04 tons/ha for young secondary forests, 39.56 tons/ha for intermediate secondary forests, and an estimated carbon reserve size of 49.44 tons/ha for mature secondary forestsEstimasi cadangan karbon pada hutan hujan tropis merupakan salah satu indikator penting dalam mengukur kesehatan ligkungan dan semakin penting dalam era mitigasi perubahan iklim. Dalam penelitian ini, menggunakan klasifikasi Normalized Difference Vegetation Index (NDVI) pada citra Sentinel-2 MSI untuk mengestimasikan cadangan karbon pada hutan hujan tropis di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Universitas Lambung Mangkurat. Citra satellite Sentinel 2 MSI digunakan untuk mendapatkan informasi nilai NDVI dan tutupan lahan, sedangkan klasifikasi NDVI digunakan untuk menghubungkan informasi tersebut dengan data lapangan perhitungan cadangan karbon. Hasil penelitian berdasarkan klasifikasi nilai Normalized Difference Vegetation Index (NDVI) di KHDTK memiliki nilai bervariasi antara 0.0716 hingga 0.83424, terdiri dari lima kelas tutupan lahan yaitu lahan terbuka, semak, perkebunan atau hutan sekunder muda, hutan sekunder sedang dan hutan sekunder tua. Besar cadangan karbon diperoleh dari 47 % biomassa yang dihitung dengan persamaan allometric yang sudah ada, pengukuran biomassa dilakukan pada diameter pohon 10 centimeter ke atas. Lima kelas tutupan lahan yang diklasifikasi diperoleh besar cadangan karbon untuk lahan terbuka 6.05 ton/ha, semak 13.40 ton/ha, Hutan sekunder muda 21.04 ton/ha, hutan sekunder sedang 39.56 ton/ha dan estimasi cadangan karbon hutan sekunder tua sebesar 49.44 ton/ha.